Pharmacological Aspects of Duloxetine: An Update - Deepak P.; Kumar T. N. (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Duloxetine is thought to block the reuptake of serotonin and norepinephrine in Onuf’s nucleus in the sacral spinal cord, thereby activating pudendal motor neurons that increase the urethral striated muscle tone and the force of sphincter contraction. Duloxetine was developed for the management of depression. This drug was later found to be effective in the treatment of Stress Urinary Incontinence. It works by preventing serotonin and norepinephrine from being reabsorbed in a region of the sacral spinal cord where these neurotransmitter receptors are highly concentrated. This stimulates particular motor neurons that control the urethral striated muscle sphincter.